2003
DOI: 10.1002/ca.10168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lithotomy positions on strain of the obturator and lateral femoral cutaneous nerves

Abstract: The purpose of this study was to determine if various lithotomy positions increase strain on the obturator and lateral femoral cutaneous nerves in fresh adult cadavers. A static load cell was used to record strain changes of the obturator and lateral femoral cutaneous nerves in the pelvis and anterior thigh when the lower limbs were placed in three sets of positions of varying hip abduction and flexion. The means of the strain measurements, which were measured in grams in all positioning angles were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…The nerve is probably injured most frequently during hip surgery due to stretch, compression by a retractor, or encasement in cement 2, 11. Although lithotomy position can strain the nerve,8 one large prospective study found that neuropathy developed in only 5 of 991 surgical patients 15. Compression of the obturator during delivery can occur from the fetal head or forceps in the pelvic canal 7.…”
Section: Discussionmentioning
confidence: 99%
“…The nerve is probably injured most frequently during hip surgery due to stretch, compression by a retractor, or encasement in cement 2, 11. Although lithotomy position can strain the nerve,8 one large prospective study found that neuropathy developed in only 5 of 991 surgical patients 15. Compression of the obturator during delivery can occur from the fetal head or forceps in the pelvic canal 7.…”
Section: Discussionmentioning
confidence: 99%
“…Kitle etkisine bağlı basılar sıklıkla obturator kanal düzeyinde veya uyluk proksimalinde herni, periartiküler kist veya bursa nedeniyle görülür. Genitoüriner cerrahilerde uzun süre litotomi pozisyonunda kalmaya, kalça cerrahisinde ise aşırı gerilmeye bağlı etkilenebilir [8]. Spor ile ilişkili obturator nöropati, obturator sinir anterior dalının adduktor brevis tendinopatisi ile ilişkili fasyal adezyona bağlı gerilmesi sonucu oluşur.…”
Section: Obturator Sinirunclassified
“…61.7 ) [ 27 ]. This angle increases with movement and hip extension; however, hip fl exion and abduction as seen in the lithotomy position does not increase strain on the LFCN [ 10 ]. The tendency for entrapment at the path between the pelvis and thigh, as well as in the thigh itself, is exacerbated by obesity, pregnancy, ascites, tight garments, seat belts, braces, direct trauma, leg length changes, scoliosis, and muscle spasm [ 25 ].…”
Section: Entrapmentmentioning
confidence: 99%